A PI/PID controller for time delay systems with desired closed loop time response and guaranteed gain and phase margins. (January 2016) - Srivastava, Saurabh; Pandit, V.S.
Highlights: A novel graphical tuning of PI/PID controller for time delay system is proposed. Method uses pole placement approach for time delay system without any approximation. Desired closed loop time response is achieved with pre specified GM and PM. The conditions for robust controller design are analyzed via simulation. Abstract: In this article we present a graphical tuning method of PI/PID controller for first order and second order plus time delay systems using dominant pole placement approach with guaranteed gain margin (GM) and phase margin (PM). The stability equation method and gain phase margin tester have been used to portray constant GM and PM boundaries. The PID controller parameters have been obtained for different dominant poles and plotted graphically in the parameters plane of controller within the specified GM and PM regions. To demonstrate the effectiveness and confirm the validity of the proposed methodology, three examples with numerical simulations are presented.